2006
DOI: 10.1158/1078-0432.ccr-05-1625
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Intraperitoneal Photodynamic Therapy for Patients with Peritoneal Carcinomatosis and Sarcomatosis

Abstract: Purpose: A previous phase I trial of i.p. photodynamic therapy established the maximally tolerated dose of Photofrin (Axcan Pharma, Birmingham, AL)-mediated photodynamic therapy and showed encouraging efficacy. The primary objectives of this phase II study were to determine the efficacy and toxicities of i.p. photodynamic therapy in patients with peritoneal carcinomatosis and sarcomatosis. Experimental Design: Patients received Photofrin 2.5 mg/kg i.v. 48 hours before debulking surgery. Intraoperative laser li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 18 publications
1
104
0
Order By: Relevance
“…Therefore, in the clinic, these agents are photoactivated intraoperatively or endoscopically. Early clinical trials demonstrated feasibility and efficacy for photodynamic therapy of peritoneal metastases (27) with the major challenge being bowel perforations resulting from a lack of tumor selectivity (38). taPIT overcomes this poor tumor selectivity and bowel toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the clinic, these agents are photoactivated intraoperatively or endoscopically. Early clinical trials demonstrated feasibility and efficacy for photodynamic therapy of peritoneal metastases (27) with the major challenge being bowel perforations resulting from a lack of tumor selectivity (38). taPIT overcomes this poor tumor selectivity and bowel toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Because photodynamic agents are mechanistically distinct from traditional treatment modalities (13,14), are effective against radioresistant and chemoresistant cells (19,20,26), and can also resensitize resistant cells to chemotherapy (20,23), the development of PIT is of importance for overcoming drug resistance. In fact, photodynamic therapy has been used in the treatment of disseminated peritoneal disease with some success intraoperatively (27) and endoscopically in the lung, bladder, and esophagus (SI Text, Note S1).…”
mentioning
confidence: 99%
“…This inherent capability to integrate imaging and PDT treatment, which makes PS imaging particularly conducive to online monitoring of therapy response, was not used in the studies referenced above. It is also worth noting that the application of PDT to the treatment of OvCa has shown promise in clinical trials (Sindelar et al, 1991;Hendren et al, 2001;Hahn et al, 2006), although further studies are warranted to establish optimal conditions for light and PS delivery in the clinic.…”
mentioning
confidence: 99%
“…There is early evidence that photosensitizing agents are taken up by peritoneal metastatic nodules, implying that PDT here is feasible, although a clinical benefit has not yet been shown (28). It is suggested that a more selective photosensitizing agent is required to improve the results, but also a better light delivery mechanism.…”
Section: Delivery Of New Therapeutic Techniquesmentioning
confidence: 99%